2021
DOI: 10.29328/journal.jnnd.1001052
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuron specific enolase as a biomarker in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is thought to be the most common neurodegenerative disease with movement disorder. The key motor symptoms are rigidity, tremor, akinesis/hypokinesia/bradykinesia, and postural instability. However, in our day-to-day clinical practice we tend to see several other symptoms which may be motor or non-motor. Non-motor symptoms (NMS) are quite common and debilitating. The pathological hallmarks of PD are loss of dopaminergic neurons in the substantia nigra pars compacta (SNPc) and accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…The most significant neuronal injury biomarker associated with MOOD and CFS symptoms in Parkinson’s disease is an increase in NSE. Increased NSE in the cerebro-spinal fluid has been suggested in some publications as a potential specific biomarker for Parkinson’s disease (Dutta, 2021). Neuronal damage (Constantinescu et al, 2009; Herrmann et al, 1999; Isgrò et al, 2015), neurodegenerative disorders such as stroke and Alzheimer’s disease (Chaves et al, 2010; Christl et al, 2019; Isgrò et al, 2015; Papuć and Rejdak, 2020), traumatic brain injury (Kim et al, 2018; Streitbürger et al, 2012), and hypoxic encephalopathy (León-Lozano et al, 2020) are all confirmed by elevated levels of NSE in serum and cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant neuronal injury biomarker associated with MOOD and CFS symptoms in Parkinson’s disease is an increase in NSE. Increased NSE in the cerebro-spinal fluid has been suggested in some publications as a potential specific biomarker for Parkinson’s disease (Dutta, 2021). Neuronal damage (Constantinescu et al, 2009; Herrmann et al, 1999; Isgrò et al, 2015), neurodegenerative disorders such as stroke and Alzheimer’s disease (Chaves et al, 2010; Christl et al, 2019; Isgrò et al, 2015; Papuć and Rejdak, 2020), traumatic brain injury (Kim et al, 2018; Streitbürger et al, 2012), and hypoxic encephalopathy (León-Lozano et al, 2020) are all confirmed by elevated levels of NSE in serum and cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal damage (Constantinescu et al, 2009; Herrmann et al, 1999; Isgrò et al, 2015), neurodegenerative disorders such as stroke and Alzheimer’s disease (Chaves et al, 2010; Christl et al, 2019; Isgrò et al, 2015; Papuć and Rejdak, 2020), traumatic brain injury (Kim et al, 2018; Streitbürger et al, 2012), and hypoxic encephalopathy (León-Lozano et al, 2020) are all confirmed by elevated levels of NSE in serum and cerebrospinal fluid. Elevated NSE levels were found to be correlated with more severe depressive symptoms in children diagnosed with transfusion-dependent thalassemia (Dutta, 2021; Ridhaa et al, 2023). Conversely, adverse observations regarding serum NSE concentrations have been documented as well (Sathe et al, 2012; Schaf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In its mitochondria-bound form, enolase acts as an RNA chaperone, binding and transporting nucleo-cytoplasmic tRNAs to mitochondria. It also contributes to stabilizing mitochondrial membrane potential by binding to VDAC1, an integral mitochondrial membrane protein Prognostic and diagnostic cancer biomarker and oncotherapeutic target [ 6 , 13 , 20 , 22 , 26 32 ] γ-enolase Enolase 2, neural enolase, neuron-specific enolase ENO2 encodes γ subunit γγ, αγ Neurons and neuroendocrine tissue, neuronal support cells Promotes neuronal survival, differentiation, and axonal regeneration Biomarker for small cell lung cancer and neuroendocrine tumors Confirmed upregulation in neurological conditions and neurodegenerative diseases [ 1 , 14 , 22 , 26 , 33 42 ] β-enolase Enolase 3, muscle-specific enolase, skeletal muscle enolase ENO3 encodes β subunit ββ, αβ Muscle Distinguishes proliferating myoblasts from various stages of development, indicating β-enolase as a marker of human myoblast heterogeneity Role in cholesterol metabolism due to accelerating hepatic cholesterol ester cumulation induced via the mediation of cholesteryl ester generation Biomarker for myoblast heterogeneity that accompanies development Marker for identifying skeletal muscle injuries and the origin of bleeding Deficiency may lead to a rare inherited metabolic myopathy caused by an enzymatic defect of distal glycolysis Increased expression was detected in rhabdomyosarcoma tissue [ 12 , 21 , 22 , 26 , 43 50 ] Enolase 4 ENOLL ENO4 / Testis Required for normal a...…”
Section: The Functional Diversity Of Enolasementioning
confidence: 99%
“…Additionally, NSE is currently recognized as the most reliable tumor marker for diagnosing, prognosing, and monitoring small-cell lung cancer [ 86 ]. NSE can be measured in cerebrospinal fluid (CSF) and serum [ 40 , 42 , 87 ]. In addition to CFS and serum NSE biomarkers, many studies have aimed to validate a plasma biomarker for neuronal damage that could be used non-invasively to study neurological diseases in both acute and chronic models [ 39 , 88 , 89 ].…”
Section: Nse As a Neuronal Biomarkermentioning
confidence: 99%
See 1 more Smart Citation